Lipotoxicity and Mitochondrial Dysfunction in Type 2 Diabetes - C. Hesselink, Matthijs K.; Mensink, Marco; Schrauwen, Patrick (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
The prevalence of pre-diabetes and type 2 diabetes increases alarmingly the last few decades and estimates indicate this rise will continue the forthcoming decades. Transition of the pre-diabetic to the diabetic state is a slow but inevitable process. It is therefore of importance to intervene in this transition period in order to prevent overt type 2 diabetes to occur. While the focus of research towards type 2 diabetes has long been glucocentric, over the last decade the focus has shifted to a more lipocentric view. Thus, subnormal fat oxidative capacity, increased mitochondrial damage (lipotoxicity) and decrease mitochondrial function and biogenesis have been identified as factors associated with type 2 diabetes. Within a mitocentric framework, we aim to evaluate the available literature on lipotoxicity and mitochondrial dysfunction and its contribution to the development of insulin resistance and finally type 2 diabetes. In addition, putative targets of intervention will be identified and the modes of action of currently available anti-diabetic agents will be reviewed. In the majority of this review the organ of interest will be the skeletal muscle, as this is the major site of insulin resistance.
Keywords: UCP3